2005
DOI: 10.1063/1.1855461
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization reversal in single-layer and exchange-biased elliptical-ring arrays

Abstract: Arrays of elliptical rings with long axis of 3μm, short axis of 1.8μm, and widths of 400nm and above were fabricated by zone-plate-array lithography and lift-off processing. Hysteresis loops of NiFe elliptical rings with different widths indicate the “vortex” state is more stable for narrower rings. Micromagnetic simulations reveal that the magnetization configurations of wider rings are more complicated than that of narrower ones. Elliptical-ring arrays fabricated from exchange-biased thin film structures dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Investigations of the role of magnetic vortices in exchange bias systems have begun only recently [27][28][29][30][31]. In previous experiments, we have shown that the interplay between the unidirectional exchange bias and vortex structures can give rise to angular-dependent magnetization reversal, when the exchange bias is established with a saturated ferromagnet [27,31].…”
mentioning
confidence: 99%
“…Investigations of the role of magnetic vortices in exchange bias systems have begun only recently [27][28][29][30][31]. In previous experiments, we have shown that the interplay between the unidirectional exchange bias and vortex structures can give rise to angular-dependent magnetization reversal, when the exchange bias is established with a saturated ferromagnet [27,31].…”
mentioning
confidence: 99%
“…The samples have been fabricated specifically for PNR experiments by using zone plate array lithography [7], [9].…”
Section: Methodsmentioning
confidence: 99%
“…3 and 4). The insets show a SEM image of small section of the sample [7], [9], and a schematic representation of the vortex and onion states. The red and blue arrows indicate the idealistic orientation of magnetization in the rings in each case.…”
mentioning
confidence: 99%
“…
Lithographically defined arrays of metallic or semiconductor nanorings with feature sizes in the sub-100 nm range have attracted great attention recently, because of their unique magnetic, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] optical, [16] or electrical properties. Several fabrication methods for ordered arrays of ring-shaped structures have been developed.
…”
mentioning
confidence: 99%
“…Several fabrication methods for ordered arrays of ring-shaped structures have been developed. [13][14][15][17][18][19][20][21][22][23][24][25][26] Conventional structuring techniques such as photo-and electron-beam lithography (EBL) are limited in spatial resolution and low throughput, respectively. Alternatively, low-cost template-based synthesis approaches for ring-shaped nanostructures have been developed very recently.…”
mentioning
confidence: 99%